Fluoride-Catalyzed Nucleophilic Addition of PhSCF2SiMe3 to Isatins: Synthesis of 3-(1′,1′-Difluoroalkyl)-3-hydroxyindolin-2-ones - Sirisuk Keereewan (2019)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim The synthesis of 3-(1′,1′-difluoroalkyl)-3-hydroxyindolin-2-ones by employing α,α-difluoro-α-phenylsulfanyl-α-trimethylsilylmethane (PhSCF2SiMe3) as a gem-difluoromethylene building block is described. The reaction involves a fluoride-catalyzed nucleophilic addition of PhSCF2SiMe3 to various isatin derivatives followed by the reductive cleavage of the phenylsulfanyl group to lead to 3-(difluoromethyl)-3-hydroxyindolin-2-ones in good yields. Under similar reduction conditions but in the presence of activated olefins, an intermolecular radical trapping reaction took place to yield 3-(1′,1′-difluoroalkyl)-3-hydroxyindolin-2-one derivatives.